A social ecological approach to identify the barriers and facilitators to COVID-19 vaccination acceptance: A scoping review. - Penny Lun; Jonathan Gao; Bernard Tang; Chou Chuen Yu; Khalid Abdul Jabbar; James Alvin Low; Pradeep Paul George (PLoS ONE)
Background COVID-19 is an infectious disease caused by the SARS-CoV-2 virus that has caused substantial impact on population health, healthcare, and social and economic systems around the world. Several vaccines have been developed to control the pandemic with varying effectiveness and safety profiles. One of the biggest obstacles to implementing successful vaccination programmes is vaccine hesitancy stemming from concerns about effectiveness and safety. This review aims to identify the factors influencing COVID-19 vaccine hesitancy and acceptance and to organize the factors using the social ecological framework. Methods We adopted the five-stage methodological framework developed by Arksey and O'Malley to guide this scoping review. Selection criteria was based on the PICo (Population, Phenomenon of interest and Context) framework. Factors associated with acceptance and hesitancy were grouped into the following: intrapersonal, interpersonal, institutional, community, and public policy factors using the social ecological framework. Results Fifty-one studies fulfilled this review's inclusion criteria. Most studies were conducted in Europe and North America, followed by Asia and the Middle East. COVID-19 vaccine acceptance and hesitancy rates varied across countries. Some common demographic factors associated with hesitancy were younger age, being female, having lower than college education, and having a lower income level. Most of the barriers and facilitators to acceptance of the COVID-19 vaccines were intrapersonal factors, such as personal characteristics and preferences, concerns with COVID-19 vaccines, history/perception of general vaccination, and knowledge of COVID-19 and health. The remaining interpersonal, institution, community, and public policy factors were grouped into factors identified as barriers and facilitators. Conclusion Our review identified barriers and facilitators of vaccine acceptance and hesitancy and organised them using the social ecological framework. While some barriers and facilitators such as vaccine safety are universal, differentiated barriers might exist for different target groups, which need to be understood if they are to be addressed to maximize vaccine acceptance.